Epidemiology of Human Rabies Deaths in Babylon Province, Five Years Descriptive Epidemiologic Study - Hasan Alwan Baiee (Journal of Global Pharma Technology, 2017)
Human rabies is a fatal zoon tic diseases, it was endemic in Iraq since 4000 BC, poor passive surveillance and lack of educational awareness of public in Iraq lead to the end emicity and outbreaks of the disease especially in the central governorates including Babylon province. The objective of this study was to evaluate the epidemiologic features and the incidence of deaths of human   rabies   in Babylon province during the years 2012 to 2016.Nine human rabies deaths were reported during this period. Diagnosis is majorly carried out by clinical presentation coupled with history of exposure to rabies infected dog. This number of human deaths due to rabies gotten from this review is a far cry to the number of human death due to the diseases. This study showed that this disease is endemic in Babylon governorate, an epidemic took place in the province during the year 2016, the victims were mainly males; male to female ratio was 8: 1, fatal human rabies affect mainly children and young age males, most of victims didn’t receive post exposure vaccine (88.9%).Human rabies in Babylon province still a public health problem, strategic plan for elimination of human rabies is strongly needed. Keywords: Epidemiology, Human rabies, deaths, Babylon, Iraq.